PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN POWTOON UNTUK PENGUATAN CINTA TANAH AIR PADA MATA PELAJARAN IPAS KELAS V SD IT AL-MINAH - Sri Rezeki Butar-Butar; Ahmad Calam; Fira Astika Wanhar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to produce Powtoon-based instructional video media that is feasible, practical, and effective in improving IPAS learning outcomes and strengthening the sense of national pride (Cinta Tanah Air) among fifth-grade students at SD IT Al-Minah. The main problem addressed is low student learning outcomes, with classical completeness reaching only 23.07% due to dependence on conventional printed media. The research method employed is Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 26 fifth-grade students. Data were collected through observations, interviews, validation questionnaires, and learning outcome tests (pre-test and post-test). The results indicate that the Powtoon animation video media is highly feasible, with material expert validation at 92% and media expert validation at 93%. The practicality level reached 93% based on assessments by educational practitioners. Furthermore, the media proved effective in improving student learning outcomes, with the average score rising from 56 to 84 and achieving 100% classical completeness. It can be concluded that Powtoon animated video media is highly feasible and effective as an innovative learning tool to enhance material mastery while internalizing the values of patriotism for elementary school students.